(untitled) (Journal of Dhaka Medical College, 2021)
Background: The COVID-19 pandemic in Bangladesh is part of the worldwide pandemic of coronavirus disease 2019 which has crowded out services for both covid and non-covid patients, in a country where the health care system was already under huge stress even before the pandemic. Objectives: To postpone non-urgent surgeries along with active surveillance of thyroid cancer patients to make sure the hospitals are not unnecessarily occupied. Methods: Document based categorization of thyroid cancer patients, like- low risk, high risk and clinically extremely vulnerable groups who are at greatest risk of severe illness from coronavirus are to be done accordingly. Individuals with thyroid cancer are mostly not susceptible to COVID- 19. However, patients with thyroid cancer (papillary or medullary) having lung metastases or undergoing certain types of cancer treatment might be at increased risk of viral infection or complications. Risk benefit ratio is checked and explained to the patient and their attendants. Recommendations: As COVID-19 is spreading across the Bangladesh, hospitals are being forced to reallocate resources to the care of critically ill. So it is crucial to adhere to the advice from experts to reduce the risk of infection. All non-essential surgeries and hospital admissions can be postponed to make sure that hospitals are not unnecessarily occupied. Conclusion: In the face of the COVID-19 pandemic, cancer care has had to adapt rapidly given recommendations to postpone nonurgent surgeries with active surveillance of thyroid cancer patients except thyroid tumors requiring acute airway management. J Dhaka Medical College, Vol. 29, No.2, October, 2020, Page 178-181